4R plant nutrient management in African agriculture: an extension handbook for fertilizer management in smallholder farming systems - Zingore, Shamie; Njoroge, S; Chikowo, Regis; Kihara, Job Maguta; Nziguheba, Generose; Nyamangara, Justice (International Plant Nutrition Institute, 2014)
The IPNI sub-Saharan Africa Program has released an extension handbook for fertilizer management in smallholder farming in sub-Saharan Africa. The innovative handbook was developed as a resource for researchers, extension agents, agrodealers and other stakeholders working with smallholder farmers. Its purpose is to ensure that researchers and extension agents working with farmers have adequate information required to demonstrate and communicate to farmers the best ways to use fertilizers and other nutrient resources. The handbook provides practical guidelines for best nutrient management based on the principles of 4R nutrient Stewardship: Applying the Right Source of nutrients ta the Right Rate, Right Time and Right Place. Download the manual via the URL link.